Sinonim, Repetisi, dan Antonim dalam Bahasa Jepang: Telaah Majalah Nihongo Journal dan Hiragana Times - Susanti, Rita; Aminah, Siti; Oktaviani, Nani (Lingua Cultura, 2009)
Purpose of this article is to know the kinds of repetition, synonym, and antonym in Japanese. Data were taken from the columns of â€œNJ Newsâ€ of Nihongo Journal magazine to analyze the repetition and columns of â€œTips for Livings in Japanâ€ in Hiraganaâ€™s Times magazine, to discuss the synonym and antonym. The research result indicates that the full repetition is often used to emphasize information; then the context synonym is used in order to create a variation of sentences. Yet, there was also information was not found in the data, which was the antonym of kobutsu no kankei because it did not explain about family.Â